2020
DOI: 10.18632/aging.102880
|View full text |Cite
|
Sign up to set email alerts
|

Secondary injury to distal regions after intracerebral hemorrhage influence neurological functional outcome

Abstract: Although many studies have focused on functional impairment after intracerebral hemorrhage, little is known about the relationship between secondary injuries to distal regions and neurological function. Our study aimed to evaluate the secondary injuries after intracerebral hemorrhage and explore their relationship to neurological functional outcome. Twenty-one patients with hemorrhages in supratentorial, deep locations and 10 healthy subjects were recruited. Longitudinal examinations of diffusion tensor imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although the hippocampus is not in situ hemorrhagic focus, a secondary injury may cause a decline of memory and cognition ability [5,6]. More recently, a clinical study has shown that ICH patients present a progressive cognitive deficit as early as the 1st week, which is correlated with the fractional anisotropy values for the ipsilateral hippocampus [7]. Furthermore, numerous preclinical studies observed cognition, emotion, and depression-related behavioral deficits in rodent models of ICH [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Although the hippocampus is not in situ hemorrhagic focus, a secondary injury may cause a decline of memory and cognition ability [5,6]. More recently, a clinical study has shown that ICH patients present a progressive cognitive deficit as early as the 1st week, which is correlated with the fractional anisotropy values for the ipsilateral hippocampus [7]. Furthermore, numerous preclinical studies observed cognition, emotion, and depression-related behavioral deficits in rodent models of ICH [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that more work is needed to improve ICH treatment and reduce the risk of death. ICH is associated with toxic metabolites in the hematoncus, which leads to neuronal dysfunction and neurologic impairment (Song et al, 2020). As for the absorption and excretion pathways of these toxic metabolites, the traditional view is that hemosiderin and necrotic brain tissues are mostly engulfed by phagocytes (Chen C. et al, 2020).…”
Section: Introductionmentioning
confidence: 99%